Evaluation of a deliberative approach to citizen involvement in health care priority setting. Issue 1 (28th January 2014) - Williams, Iestyn; Phillips, Daisy; Nicholson, Charles; Shearer, Heather
Abstract : Purpose: – The purpose of this paper is to describe and evaluate a novel approach to citizen engagement in health priority setting carried out in the context of Primary Care Trust (PCT) commissioning in the English National Health Service. Design/methodology/approach: – Four deliberative events were held with 139 citizens taking part in total. Events design incorporated elements of the Twenty-first Century Town Meeting and the World Café, and involved specially-designed dice games. Evaluation surveys reporting quantitative and qualitative participant responses were combined with follow-up interviews with both PCT staff and members of the public. An evaluation framework based on previous literature was employed. Findings: – The evaluation demonstrates high levels of enjoyment, learning and deliberative engagement. However, concerns were expressed over the leading nature of the voting questions and, in a small minority of responses, the simplified scenarios used in dice games. The engagement exercises also appeared to have minimal impact on subsequent Primary Care Trust resource allocation, confirming a wider concern about the influence of public participation on policy decision making. The public engagement activities had considerable educative and political benefits and overall the evaluation indicates that the specific deliberative tools developed for the exercise facilitated a high level of discussion. Originality/value: – This paper helps to fill the gap in empirical evaluations of deliberative approaches to citizen involvement in health care priority setting. It reports on a novel approach and considers a range of implications for future research and practice. The study raises important questions over the role of public engagement in driving priority setting decision making.